Desarrollo psicomotor y su relación con el estado nutricional en los niños de 6 a 24 meses del proyecto Ally Micuy De ADRA en Huari, Ancash, 2009 - Jeaneth Beltrán Huayta (2019)
Objective: The objective of this research was determine the relationship that exists between psychomotor development and nutritional status in children from 6 to 24 months of the Ally Micuy Project, of ADRA in Huari, Ancash, 2009. Methodology: The methodology correspond to a not experimental desing, descriptive correlation type,transverse cut. The studied population were conformed for 170 children from 6 to 24 months of the Huari district,from these were select to 80 children by sampling simple random stratified probability. The instruments used forgathering data were: The Assessment Scale of Psychomotor Development (EEDP), Results: The Anthropometricevaluation Sheet and a survey. The data analysis for the nutritional diagnosis was with the software “WHO Anthro2007”, for the hypothesis test, the statistical analysis of nonparametric type, Chi square Χ2. Results: The resultsshow that the psychomotor development level is normal in 53,8%; 37,5% correspons to the risk level and only 8,8%delay. Talking about the nutritional status, according to the standar WHO 2006, in the indicators L/A, W/L, W/Awas normal in 30%, 62,5%, 66,3% repectively. 23,8% presents chronic malnutrition, none has acute malnutrition,22,5% overweight and 6,3% obesity. Conclusions: Concluding that there is not connection between psychomotordevelopment and nutritional status in children from 6 to 24 months of the Ally Micuy Project, of ADRA in Huari,Ancash. Length for age (p=0,529), Weight for length (p=0,830), Weight for age (p= 0,891).